2021
DOI: 10.3390/app11062656
|View full text |Cite
|
Sign up to set email alerts
|

How to Make Augmented Reality a Tool for Railway Maintenance Operations: Operator 4.0 Perspective

Abstract: In the last few decades, several initiatives and approaches are set up to support maintenance procedures for the railway industry in adopting the principles of Industry 4.0. Contextualized maintenance technologies such as Augmented Reality (AR) overlay can integrate virtual information on physical objects to improve decision-making and action-taking processes. Operators work in a dynamic working environment requiring both high adaptive capabilities and expert knowledge. There is a need to support the operators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Examples of the use of AR include bus maintenance systems (e.g., [ 232 ]), power plant maintenance (e.g., [ 233 ]), railway systems (e.g., [ 234 ]), and military systems (e.g., [ 235 ]). The concept of a system for assisting diagnostic processes using AR technology was presented among others in works [ 236 , 237 ].…”
Section: Systematic Literature Review Of the Selected Papers Within T...mentioning
confidence: 99%
“…Examples of the use of AR include bus maintenance systems (e.g., [ 232 ]), power plant maintenance (e.g., [ 233 ]), railway systems (e.g., [ 234 ]), and military systems (e.g., [ 235 ]). The concept of a system for assisting diagnostic processes using AR technology was presented among others in works [ 236 , 237 ].…”
Section: Systematic Literature Review Of the Selected Papers Within T...mentioning
confidence: 99%
“…In 1968, Ivan Sutherland, an electronics engineer at Harvard University, created the first HMD, The Sword of Damocles. This device was able to convey visual effects, sounds, and smells to the user [8]. As computers at the time were quite limited, it was only possible to see wireframes in real time.…”
Section: History Of Augmented Realitymentioning
confidence: 99%
“…In general, augmented reality contributes to standardization as well as to friendlier and more efficient workflows through the use of contextualized and personalized information [8]. In areas such as maintenance, where all processes of learning, training, and communication imply investment, decreasing the down time of equipment can help to provide greater returns on direct financial investments.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, most of the AR application cases for maintenance in the railway vehicle sector have been developed mainly on main mechanical equipment such as boogie and braking devices conducted by the research group of the National University of Transportation in Korea [23,24]. In the case of the air compressor conducted in this study, only some applications have been reported to manufacture industrial screw-type air compressors [25]. Therefore, this study aims to make it easy to use for train fleet maintenance by gradually converting important railway vehicle equipment, a collection of complex technologies such as mechanical engineering, electrical, communication, and electronic engineering, over several years to innovate existing manual-based maintenance methods in the railway industry.…”
Section: Introductionmentioning
confidence: 98%